The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.656456
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Disruption Is Not Associated With Disease Aggressiveness in Amyotrophic Lateral Sclerosis

Abstract: The pathogenesis of the fatal neurodegenerative condition amyotrophic lateral sclerosis (ALS) remains to be fully understood. Blood–brain barrier damage (BBBD) has been implicated as an exacerbating factor in several neurodegenerative conditions, including ALS. Therefore, this cross-sectional study used the novel D50 progression model to assess the clinical relevance of BBBD within a cohort of individuals with either ALS (n = 160) or ALS mimicking conditions (n = 31). Routine laboratory parameters in cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…It relies on the assumption of therapeutic extravasation from the vascular compartment to the CNS parenchyma and then to the subarachnoid space without direct CSF excretion at the choroid plexus (i.e., via the BCSFB) or complete therapeutic metabolism within neural tissue. Pharmacokinetic studies investigating CSF/serum concentration ratios of multiple ALS therapeutics have typically demonstrated low CSF/serum ratios suggesting limited therapeutic access across the BCNSB (Sussmuth et al, 2010 ; Wu et al, 2020 ; Prell et al, 2021 ; Waters et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It relies on the assumption of therapeutic extravasation from the vascular compartment to the CNS parenchyma and then to the subarachnoid space without direct CSF excretion at the choroid plexus (i.e., via the BCSFB) or complete therapeutic metabolism within neural tissue. Pharmacokinetic studies investigating CSF/serum concentration ratios of multiple ALS therapeutics have typically demonstrated low CSF/serum ratios suggesting limited therapeutic access across the BCNSB (Sussmuth et al, 2010 ; Wu et al, 2020 ; Prell et al, 2021 ; Waters et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, patients with the bulbar phenotype worsen rapidly, but they do not manifest the same effects on the BBB and BSCB dysfunction parameters measured in our study and altered in the spinal onset ALS cohort showing the elevation of CSF proteins and QAlb. These results are reinforced by Prell et al, who also found an association with increased levels of albumin in CSF, spinal-onset disease and BBB damage [ 39 ].…”
Section: Discussionmentioning
confidence: 69%
“…The gadolinium leakage normalized within 24 h, showing the reversibility of the procedure but also the absence of signs of previous BBB disruption in these patients. Moreover, elevation of QAlb has been reported in only 20–50% of ALS patients, suggesting that BBB disruption would not appear in all individuals [ 34 , 35 , 36 ]. Recently, Waters et al showed that BSCB disruption, evidenced by hemoglobin leakage in postmortem human tissues, would be predominant in the thoracic spinal cord while motoneurons loss and TDP-43 deposits were mainly observed in the cervical and lumbar spinal cord.…”
Section: Bbb Alterations In Als and Their Consequencesmentioning
confidence: 99%
“…Moreover, CSF total protein, CSF IgG, and QIgG were significant indicators of disease progression. On the other side, Prell et al evaluated the QAlb in a cohort of 160 ALS patients and 31 ALS mimicking conditions but did not find any significant association with the disease evolution [ 34 ].…”
Section: Bbb Alterations In Als and Their Consequencesmentioning
confidence: 99%